Development Strategy of Kebun Jagung Yoyo as a Tourism Object in Tarumajaya District of Bekasi Regency - Puspa Danita; Abubakar Abubakar; I Putu Eka Wijaya (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2023)
This research aims to identify internal and external factors, analyze what strategies can be implemented and what strategies are recommended in an effort to develop Yoyo Corn Garden as a tourist attraction. Research was conducted at the Yoyo Corn Garden natural tourist attraction in Tarumajaya District, Bekasi Regency. The problem that occurs is that the number of visitors continues to decline every week. The decrease in the number of visitors was caused by a lack of promotion, facilities and management knowledge to manage the business which was not yet optimal. The method used in this research is SWOT analysis using the IFAS, EFAS matrices and the grand strategy matrix. In every environmental analysis there are several factors in it, namely strengths, weaknesses, opportunities and threats. The results of this research in the SWOT analysis obtained 9 alternative strategies that can be used. The results of calculating the total score on the IFAS matrix are 1.50 and the total score on the EFAS matrix is ​​1.29, this shows that the opportunities and strengths that are owned can overcome weaknesses and threats well. The position of Yoyo Corn Plantation in the grand strategy matrix is ​​in quadrant I (one), so the strategy that will be recommended to be implemented is an aggressive strategy using the SO (strength - opportunity) strategy by utilizing internal strengths to maximize existing opportunities in an effort to develop Yoyo Corn Plantation as an object. tour.